Character-Based Education Religious Values with Challenges in the Digital Age - Aprilia, Nabila Dwi; Wahab, Wahab (Jurnal Pengabdian Nusantara, 2025)
Character education is essential for shaping online ethics in Generation Z, who grow up in a digitally connected environment. Challenges from foreign cultures and digital influences risk altering their norms and character. Islamic education, based on religious values, plays a role in building strong character to counter the negative impacts of digitalization. This study uses a literature review to analyze the role of religious character education in the digital era. Character education, grounded in Pancasila and Islamic teachings, aims to create ethical, responsible, and integrity-driven individuals. Challenges include exposure to negative content and social media. The internalization of religious values helps protect students from the negative effects of the digital world, enhances digital literacy, and guides them in discerning information wisely. Teachers are expected to adapt their teaching methods to support students' character development in this digital age.